Application of quality function deployment in redesigning website: a case study on TV3 - Islam, Rafikul; Ahmed, Mohiuddin; Alias, Masliza (Inderscience Enterprises Ltd., 2007)

(untitled)
Internet technology has been used by most of the organizations in the world today. One of the primary vehicles of information gathering and dissemination in today’s world is organizational website. This research evaluates the performance of the present TV3 (a popular private television station in Malaysia) website. By means of an on-line survey and a few focus group discussions, it also identifies the website viewer requirements and their corresponding importance level. Subsequently, the technical requirements are identified that can fulfill the viewer requirements. A House of Quality (HOQ) is built to find the relationship between the viewer and technical requirements. The Quality Function Deployment (QFD) exercise provides the prioritized technical requirements, which is expected to guide the TV3 website development and maintenance team in its future website redesigning project. The findings of the research are also expected to provide some insight in other organizations in similar need.